Early versus delayed coronary angiography in patients with out-of-hospital cardiac arrest and no ST-segment elevation: a systematic review and meta-analysis of randomized controlled trials - Hamidi, Fardin; Anwari, Elaaha; Spaulding, Christian; Hauw-Berlemont, Caroline; Vilfaillot, Aurélie; Viana-Tejedor, Ana; Kern, Karl B.; Hsu, Chiu-Hsieh; Bergmark, Brian A.; Qamar, Arman; Bhatt, Deepak L.; Furtado, Remo H. M.; et al. (Clinical research in cardiology, 2023)
Background: Recent randomized controlled trials did not show benefit of early/immediate coronary angiography (CAG) over a delayed/selective strategy in patients with out-of-hospital cardiac arrest (OHCA) and no ST-segment elevation. However, whether selected subgroups, specifically those with a high pretest probability of coronary artery disease may benefit from early CAG remains unclear. Methods: We included all randomized controlled trials that compared a strategy of early/immediate versus delayed/selective CAG in OHCA patients and no ST elevation and had a follow-up of at least 30 days. The primary outcome of interest was all-cause death. Odds ratios (OR) were calculated and pooled across trials. Interaction testing was used to assess for heterogeneity of treatment effects. Results: In total, 1512 patients (67 years, 26% female, 23% prior myocardial infarction) were included from 5 randomized controlled trials. Early/immediate versus delayed/selective CAG was not associated with a statistically significant difference in odds of death (OR 1.12, 95%-CI 0.91–1.38), with similar findings for the composite outcome of all-cause death or neurological deficit (OR 1.10, 95%-CI 0.89–1.36). There was no effect modification for death by age, presence of a shockable initial cardiac rhythm, history of coronary artery disease, presence of an ischemic event as the presumed cause of arrest, or time to return of spontaneous circulation (all P-interaction > 0.10). However, early/immediate CAG tended to be associated with higher odds of death in women (OR 1.52, 95%-CI 1.00–2.31, P = 0.050) than in men (OR 1.04, 95%-CI 0.82–1.33, P = 0.74; P-interaction 0.097). Conclusion: In OHCA patients without ST-segment elevation, a strategy of early/immediate versus delayed/selective CAG did not reduce all-cause mortality across major subgroups. However, women tended to have higher odds of death with early CAG.